1930
DOI: 10.1084/jem.51.2.295
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Specificity of Chemically Altered Proteins

Abstract: The immunological specificity of protein antigens has interesting aspects from the chemical viewpoint. Protein specificity appears to be closely associated with, and dependent on, chemical differences in the protein molecules. In most instances these differences are such that it is not possible to distinguish between similar proteins of different species by the usual methods of chemical investigation, but there are instances in which such a differentiation is possible by chemical or physical as well as by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1932
1932
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…of 7 % NH40H solution, and treated with N/10 iodine solution until there was a considerable excess of iodine [cf. Wormall, 1930]. The iodinated proteins were precipitated by the addition of 10% acetic acid to give maximum precipitation, and the precipitated protein was removed by centrifuging.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…of 7 % NH40H solution, and treated with N/10 iodine solution until there was a considerable excess of iodine [cf. Wormall, 1930]. The iodinated proteins were precipitated by the addition of 10% acetic acid to give maximum precipitation, and the precipitated protein was removed by centrifuging.…”
Section: Methodsmentioning
confidence: 99%
“…The products of this reaction react immunologically like proteins nitrated by a method which does not involve treatment with strong acid, viz. the tetranitromethane method [Wormall, 1930] Immunisation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although one would expect to obtain eventually a protein sensitization of animals injected with a material of this nature, no untoward reactions have been noted following its daily injection in mice over a period of several weeks. In this connection it is interesting to note that Wormall (34) reported that proteins lose their antigenic specificity when iodinated and acquire a new specificity for iodoprotein.…”
Section: Historical Backgroundmentioning
confidence: 99%